2017
DOI: 10.2471/blt.16.179556
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a social franchising and telemedicine programme and the care provided for childhood diarrhoea and pneumonia, Bihar, India

Abstract: ObjectiveTo evaluate the impact on the quality of the care provided for childhood diarrhoea and pneumonia in Bihar, India, of a large-scale, social franchising and telemedicine programme – the World Health Partners’ Sky Program.MethodsWe investigated changes associated with the programme in the knowledge and performance of health-care providers by carrying out 810 assessments in a representative sample of providers in areas where the programme was and was not implemented. Providers were assessed using hypothet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…A similar strategy was used to assess whether a social franchising and telemedicine intervention improved the quality of childhood illness management in Bihar, India. The study found zero improvements in the clinical management of childhood illnesses using SPs 31…”
Section: Research Examples With the Sp Methodsmentioning
confidence: 89%
“…A similar strategy was used to assess whether a social franchising and telemedicine intervention improved the quality of childhood illness management in Bihar, India. The study found zero improvements in the clinical management of childhood illnesses using SPs 31…”
Section: Research Examples With the Sp Methodsmentioning
confidence: 89%
“…We analyse data from provider quality assessments undertaken as part of baseline surveys conducted for the Bihar Evaluation of Social Franchising and Telemedicine (BEST) project—an evaluation of a large telemedicine programme funded by the Bill and Melinda Gates Foundation in Bihar. 15 …”
Section: Methodsmentioning
confidence: 99%
“…Our study evaluates a social franchising system, which is currently popular among global health actors despite the lack of sound empirical evidence on its role or effects. 41 It incorporates an account of components that would improve the regulation of drug shops and retail health markets and forge formal linkages to government health services, which is missing in previous studies. 5 38 40 Lastly, it evaluates the iCCM of childhood febrile illnesses rather than just malaria tests.…”
Section: Introductionmentioning
confidence: 99%